P.126 Cyberknife radiosurgery for trigeminal neuralgia: a retrospective review of 168 cases. (June 2022) - Guillemette, A; Fournier-Gosselin, M; David, R; Cynthia, M
Abstract : Background: Gamma Knife radiosurgery for the treatment of refractory trigeminal neuralgia is recognized as an efficient intervention. The CyberKnife, a more recent frameless radiosurgery alternative, has not been studied as extensively for this condition. The aim of this study is to evaluate the clinical outcomes of a first CyberKnife radiosurgery treatment on patients with medically refractory trigeminal neuralgia. Methods: A retrospective study of 166 patients (168 cases) with refractory trigeminal neuralgia treated since 2009 with CyberKnife radiosurgery at the Centre Hospitalier de l'Université de Montreal (CHUM). Results: Adequate pain relief (Barrow Neurological Institute (BNI) pain scores I-IIIb) was achieved in 146 cases (86.9%). The median latency period before adequate pain relief was 35 days (range 0-202 days). The median duration of adequate pain relief was 15.8 months (range 0.6-85.0[DR1] [AG2] [AG3] [AG4] months). The actuarial rates of maintenance of adequate pain relief at 12, 36, and 60 months were 77.0%, 62.5%, and 50.2%, respectively. There was a new-onset or aggravation of facial numbness in 44 cases (26.2%). The maintenance of an adequate pain relief was more sustained in idiopathic cases in comparison to cases associated with multiple sclerosis ( P< 0.001). Conclusions: In our experience CyberKnife radiosurgery for refractory trigeminal neuralgia is efficacious and safe.